Youth Criminal Justice Policy: "What Works"? - Radulović, Ljiljana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
The key goal of the youth criminal justice policy is to search for consistently efficient, coherent and cost-effective crime reduction models and instruments. The most established differentiation between systems of youth justice around the world is that of welfare versus justice. These models are "ideal types", intended to serve solely as "conceptual tools". Every country combines some elements of welfare and justice models. For example, some elements of welfarism in juvenile penal policy exist in predominant justice systems and serve the same interest: reduction of crime. In several neo- liberal countries, among them in SAD, with a predominant justice model and neo-conservatism, some alternative diversion programs continued to exist, very much connected with welfare philosophy. Although it is simply not possible to directly transfer youth justice systems from one country to another, one country can learn and transfer some aspect from policies and practices from another. Certainly, Cook County Juvenile Probation and Court Services Programs and Initiatives are positive lessons; some of the programs are very much transferable. Some of these programs have been directly responsible for reducing overcrowding at Cook County's Juvenile Detention Centre. These programs all promote principles of public safety, accountability and positive development of youth, to become more responsible and productive members of the community.